2020
DOI: 10.1016/j.mayocp.2020.04.037
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a 20-Minute Animal-Assisted Activity Session on the Physiological and Emotional States in Patients With Fibromyalgia

Abstract: Objective: To study the direct physiological and emotional impact of an animal-assisted activity (AAA) session (a form of complementary and integrative medicine) in patients with fibromyalgia (FM).Patients and Methods: The study population consisted of 221 participants with FM who were attending Mayo Clinic's Fibromyalgia Treatment Program between August 5, 2017, and September 1, 2018. This was a randomized controlled trial. Participants were randomly assigned to either the treatment group (a 20-minute session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 53 publications
0
26
1
Order By: Relevance
“…A recent randomized controlled trial similarly found that interacting with a therapy dog, for 20 min, two times per week, over a 4-week period resulted in reduced cortisol (basal and diurnal measurement) among typically developing and special needs school children compared to the same duration and length of delivery for a yoga relaxation or a classroom as usual control group ( 61 ). However, it is of note that many methodologically rigorous studies have not found significant effects of interacting with a dog on physiological parameters, including salivary cortisol ( 21 , 62 , 63 ). A recent review of salivary bioscience research in human-animal interaction concluded that significant variation exists with regards to sampling paradigms, storage and assaying methods, and analytic strategies, contributing to variation in findings across the field ( 57 ).…”
Section: Theoretical Framework For Dog Interaction Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent randomized controlled trial similarly found that interacting with a therapy dog, for 20 min, two times per week, over a 4-week period resulted in reduced cortisol (basal and diurnal measurement) among typically developing and special needs school children compared to the same duration and length of delivery for a yoga relaxation or a classroom as usual control group ( 61 ). However, it is of note that many methodologically rigorous studies have not found significant effects of interacting with a dog on physiological parameters, including salivary cortisol ( 21 , 62 , 63 ). A recent review of salivary bioscience research in human-animal interaction concluded that significant variation exists with regards to sampling paradigms, storage and assaying methods, and analytic strategies, contributing to variation in findings across the field ( 57 ).…”
Section: Theoretical Framework For Dog Interaction Benefitsmentioning
confidence: 99%
“…In fact, calming tactile interactions such as stroking, touching, and petting may be a key mechanism explaining animal-specific benefits to stress physiology, as touch is more socially appropriate in interactions with animals than as with other people ( 22 ). While there are many hypothesized mechanisms underlying positive psychophysiological change following human-dog interaction, more research is needed to determine how individual differences in humans, animals, and the human-animal relationship affects outcomes ( 21 , 57 , 62 , 63 ).…”
Section: Theoretical Framework For Dog Interaction Benefitsmentioning
confidence: 99%
“…Over the course of five sessions, no changes in cortisol or oxytocin emerged; heart rates and right tympanic ear membrane temperatures were significantly lower post-session, indicating a neutral to emotionally positive reaction towards the sessions. These novel findings indicate dogs were possibly in a more relaxed state at the end of the AAI session [23].…”
Section: Description Of Study Outcomesmentioning
confidence: 73%
“…In another recent study, Clark et al [23] used multiple parameters to assess the emotional state in therapy dogs including salivary cortisol, oxytocin, tympanic ear membrane temperature, heart rate and heart rate variability as indicators of well-being. Nineteen dogs participated in both single recipient and group therapy sessions with patients diagnosed with fibromyalgia.…”
Section: Description Of Study Outcomesmentioning
confidence: 99%
“…Potential biological mechanisms of the most common sensory-based interventions used in clinical practice and in animal models.Preclinical studies not possible, but dogs involved in AAT had ↓ heart rate and tympanic membrane temperature post-session, suggesting a more relaxed state[102] Gradual ↓ in saliva cortisol levels in patients with mild to moderate dementia, compared to controls,[97], ↑ salivary oxytocin after single session[103], a ↑ blood βendorphin, oxytocin, prolactin, and dopamine, ↓ blood cortisol after interaction with dog [104] a , ↓ in heart rate (only in healthy participants, but not in patients[105] a …”
mentioning
confidence: 99%